Digital literacy impacts quality of life among older adults through hierarchical mediating mechanisms - Yang Xin; Hu Weina; Deng Yan (Scientific Reports)
Abstract The rapid digitalization of society poses significant challenges for older adults’ well-being, yet the mechanisms linking digital literacy to quality of life remain poorly understood. While previous research has examined direct relationships between digital literacy and well-being outcomes, the potential mediating roles of domain-specific capabilities and psychological resources have been overlooked. This study investigates these complex pathways through a sequential mediation model using structural equation modeling with data from 1,016 older adults (Mage = 67.11, SD = 5.92). Results revealed that digital literacy influences quality of life through multiple pathways: direct effects (β = 0.56, P < 0.01, 73.68% of total effect), parallel mediation through eHealth literacy (11.84%) and self-efficacy (10.53%), and a sequential mediation pathway (3.95%) where digital literacy enhances eHealth literacy, which subsequently strengthens self-efficacy. These findings advance the Technology-Enhanced Psychological Empowerment Model by demonstrating how domain-specific competencies and psychological resources work in concert to translate digital literacy into enhanced quality of life outcomes among older adults, providing crucial insights for designing more effective digital literacy interventions.